THE ANALYSIS OF DICTION IN THE TRANSLATED NEWS TEXT BY THE NATIONAL NEWS AGENCY OF ANTARA - Nurhendi Nurhendi (JIPIS, 2019)
Abstract This research paper is the analysis of news translation text taken place in the National News Agency of Antara. The major problems in this research are to know the use of connotative word with positive tone and the use of euphimism approach in the news translation process. The primary source is the news translation texts. The writer analyse 26 texts out of the hundreds of news translation texts produced in he period of May – August 2016. This research uses qualitative research method. The data are collected, classified, identified and explained by giving the evidence from the sentences.Based on the research, the writer concludes that journalists in the National News Agency of Antara sometimes use connotative words and euphimismistic words in their translation process. Keywords: connotative words, euphimism, translated texts